2022
DOI: 10.3389/fnagi.2022.792778
|View full text |Cite
|
Sign up to set email alerts
|

Combined Application of Quantitative Susceptibility Mapping and Diffusion Kurtosis Imaging Techniques to Investigate the Effect of Iron Deposition on Microstructural Changes in the Brain in Parkinson’s Disease

Abstract: ObjectivesBrain iron deposition and microstructural changes in brain tissue are associated with Parkinson’s disease (PD). However, the correlation between these factors in Parkinson’s disease has been little studied. This study aimed to use quantitative susceptibility mapping combined with diffusion kurtosis imaging to investigate the effects of iron deposition on microstructural tissue alterations in the brain.MethodsQuantitative susceptibility mapping and diffusion kurtosis imaging were performed on 24 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 74 publications
0
3
0
Order By: Relevance
“…A recent systematic review (Ravanfar et al, 2021 ) examining 37 studies provides valuable insight into susceptibility changes in PD. The great majority of these studies reported increased susceptibility in the brains of PD patients, mainly in the SN (30 studies) but also in the red nucleus (seven studies), putamen (Xu et al, 2021 ), globus pallidus (Yang et al, 2022 ), caudate nucleus (Uchida et al, 2019 ), and thalamus (Shahmaei et al, 2019 ). Only a few studies documented cortical increase of susceptibility, mainly in the frontal, parietal, temporal, and insular cortices (Acosta‐Cabronero et al, 2017 ; Thomas et al, 2021 ; Uchida et al, 2019 ; Zhao, Qu, et al, 2022 ), predominantly in patients with longer disease duration (7, 6, and 4 years) and/or cognitive impairment.…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review (Ravanfar et al, 2021 ) examining 37 studies provides valuable insight into susceptibility changes in PD. The great majority of these studies reported increased susceptibility in the brains of PD patients, mainly in the SN (30 studies) but also in the red nucleus (seven studies), putamen (Xu et al, 2021 ), globus pallidus (Yang et al, 2022 ), caudate nucleus (Uchida et al, 2019 ), and thalamus (Shahmaei et al, 2019 ). Only a few studies documented cortical increase of susceptibility, mainly in the frontal, parietal, temporal, and insular cortices (Acosta‐Cabronero et al, 2017 ; Thomas et al, 2021 ; Uchida et al, 2019 ; Zhao, Qu, et al, 2022 ), predominantly in patients with longer disease duration (7, 6, and 4 years) and/or cognitive impairment.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, these sequences are sensitive to iron deposition but cannot distinguish their boundaries well. Therefore, the dense and reticular zones of the substantia nigra are mostly used to analyze the iron deposition content to judge the degree of neuronal degeneration ( 17 , 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…Iron deposition significantly increases in the bilateral SN, red nucleus (RN), putamen, and globus pallidus of PD patients. Iron deposition is likely a common mechanism underlying microstructural alterations in the SN and putamen of PD patients (Yang et al 2022 ). The dysfunction of dopaminergic striatal pathways and the loss of cells in the SN pars compacta are intricately linked to the elevated iron content in the SN (Biondetti et al 2021 ).…”
Section: Iron Deposition and Pdmentioning
confidence: 99%